Description of Jolyelmis spangleri a new species from Churí-tepui (Chimantá Massif, Venezuela), with a description of the larva of J. spangleri and J. reitmaieri (Insecta: Coleoptera: Elmidae) - Kodada, Ján; Derka, Tomáš; Čiampor, Fedor (Zootaxa, 2012)
Four species have been recognized in the genus Jolyelmis Spangler & Faitoute; all collected at isolated table mountains,mostly in cool stenothermal hypocrenal streams. The known distribution of the genus is confined to Venezuela, and eachspecies is here reported as endemic for the respective table mountain where it has been found. Samples from Churí-tepuiand Mount Roraima in south-eastern Venezuela contained numerous adults and larvae of Elmidae among which is a newspecies, Jolyelmis spangleri, which is here described. The new species is illustrated and keyed with all other Jolyelmis,and new distributional data for J. reitmaieriČiampor, Jr. & Kodada are included. Molecular analysis of partial cytochromeoxidase subunit I (cox1) confirmed conspecific life stages for two species: J. spangleri and J. reitmaieri. The larva of eachspecies is described and illustrated, and the generic diagnosis for Jolyelmis larvae is provided. Among the known larvaeof South American Elmidae, larvae of the genus Xenelmis Hinton appear to be the most similar. Morphological similarities are discussed. Habitats of adults and larvae are briefly described and illustrated by photographs.